2014
DOI: 10.1128/aem.02848-13
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Iron by Sulfate-Reducing Bacteria: New Views of an Old Problem

Abstract: About a century ago, researchers first recognized a connection between the activity of environmental microorganisms and cases of anaerobic iron corrosion. Since then, such microbially influenced corrosion (MIC) has gained prominence and its technical and economic implications are now widely recognized. Under anoxic conditions (e.g., in oil and gas pipelines), sulfate-reducing bacteria (SRB) are commonly considered the main culprits of MIC. This perception largely stems from three recurrent observations. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
445
0
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(471 citation statements)
references
References 114 publications
5
445
0
21
Order By: Relevance
“…Besides methanogenic archaea and homoacetogenic bacteria, Fe(0)-corroding microorganisms have been intensively investigated for their outstanding electron transfer capabilities (Dinh et al, 2004;Uchiyama et al, 2010;Enning et al, 2012;Venzlaff et al, 2013;Enning and Garrelfs, 2014;Kato et al, 2015;Beese-Vasbender et al, 2015b). Although direct electron uptake has been proposed in these microorganisms, no mechanism has been identified to date Venzlaff et al, 2013;Enning and Garrelfs, 2014;BeeseVasbender et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Besides methanogenic archaea and homoacetogenic bacteria, Fe(0)-corroding microorganisms have been intensively investigated for their outstanding electron transfer capabilities (Dinh et al, 2004;Uchiyama et al, 2010;Enning et al, 2012;Venzlaff et al, 2013;Enning and Garrelfs, 2014;Kato et al, 2015;Beese-Vasbender et al, 2015b). Although direct electron uptake has been proposed in these microorganisms, no mechanism has been identified to date Venzlaff et al, 2013;Enning and Garrelfs, 2014;BeeseVasbender et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Можливо, корозійний процес за наявності цього штаму від-бувається за механізмом катодної деполяризації [3,5,8]. Порівнюючи швидкість корозії з продукуванням сірководню, можемо припусти-ти, що біокорозія за наявності вищевказаних штамів сульфатвідновлювальних бак-терій може відбуватися за різними механізмами: катодної і анодної деполяризації.…”
Section: рис 2 продукування сірководню сульфатвідновлювальними бактunclassified
“…В останні роки з'явилися дані, що корозійна агресивність різних родів сульфатвідновлювальних бактерій дуже варіабельна і може бути у представників одного роду від високої до практично невираженої та залежить від індивідуальних особливостей штаму [4,5]. Зважаючи на зазначене вище, метою цієї роботи було вивчення метаболічної та корозійної активності сульфатвідновлювальних бактерій, виділених із різних екотопів.…”
unclassified
“…Many industries employing buried pipelines and interred structures made a great effort on study the microbial induced corrosion (Iverson 1987;Ford and Mitchell 1990;Lavania et al 2011;Enning and Garrelfs 2014), where SRB play an important role (Crombie et al 1980;Pankhania 1988;Lee et al 1995;Hao et al 1996). Moreover, recent investigations showed that SRB rapidly and massively change the injectivity in the near well bore area Zettlitzer et al 2010).…”
Section: Carbon Availability and Environmental Conditions Control Micmentioning
confidence: 99%